Delayed Donor Bone Marrow Infusion Induces Liver Transplant Tolerance. Issue 5 (May 2017) - Xie, Yan; Wu, Yang; Xin, Kang; Wang, Jiao-Jing; Xu, Hong; Ildstad, Suzanne T.; Leventhal, Joseph; Yang, Guang-Yu; Zhang, Zheng; Levitsky, Josh
Abstract : Background: Nonmyeloablative conditioning followed by donor bone marrow infusion (BMI) to induce tolerance has not been robustly tested in liver transplantation (LT) and may be unsafe at the time of LT. We hypothesized T cell–depleted BMI is effective in inducing tolerance when delayed after LT, resulting in potentially safer future clinical applications. Methods: Nonimmunosuppressed syngeneic (Lewis to Lewis) and allogeneic (ACI to Lewis) rat LT transplants were initially performed as controls. Three experimental allogeneic LT groups were treated with tacrolimus (TAC) for 3 to 4 weeks and then underwent: (1) TAC withdrawal alone; (2) nonmyeloablative conditioning (anti-αβTCR mAb + total body irradiation [300 cGy]) followed by TAC withdrawal; (3) Nonmyeloablative conditioning + donor BMI (100 × 10 6 T cell–depleted bone marrow cells) followed by TAC withdrawal. Results: All group 1 recipients developed chronic rejection. Group 2 had long-term survival but impaired liver function and high donor-specific antibody (DSA) levels. In contrast, group 3 (conditioning + BMI) had long-term TAC-free survival with preserved liver function and histology, high mixed chimerism and blood/liver/spleen CD4 + CD25 + Foxp3+ regulatory T cells, and low DSA titers, similar to syngeneic grafts. While donor-specific tolerance was observed post-BMI, graft-versus-host disease was not. Conclusions: These results support that donor-specific tolerance can be achieved with BMI even when delayed after LT and this tolerance correlates with increased mixed chimerism, regulatory T cell generation, and diminished DSA. Abstract : The authors demonstrate that donor-specific tolerance can be achieved with BMI even when delayed after liver transplantation and this tolerance may correlate with increased mixed chimerism, Treg generation, and diminished DSA. Supplemental digital content is available in the text.